2020
DOI: 10.1007/s00330-020-07345-z
|View full text |Cite
|
Sign up to set email alerts
|

The accuracy of teleradiologists in diagnosing COVID-19 based on a French multicentric emergency cohort

Abstract: Objectives To evaluate the accuracy of diagnoses of COVID-19 based on chest CT as well as inter-observer agreement between teleradiologists during on-call duty and senior radiologists in suspected COVID-19 patients. Materials and methods From March 13, 2020, to April 14, 2020, consecutive suspected COVID-19 adult patients who underwent both an RT-PCR test and chest CT from 15 hospitals were included in this prospective study. Chest CTs were immediately interpreted by th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 17 publications
1
17
0
Order By: Relevance
“…Regarding diagnosis purpose, in some studies, teleconsultation services were used by physicians to do diagnosis procedures. In some other studies, an attempt was made to perform the diagnosis process with the patients' participation accurately ( 7 , 42 , 60 , 62 ).…”
Section: Discussionmentioning
confidence: 99%
“…Regarding diagnosis purpose, in some studies, teleconsultation services were used by physicians to do diagnosis procedures. In some other studies, an attempt was made to perform the diagnosis process with the patients' participation accurately ( 7 , 42 , 60 , 62 ).…”
Section: Discussionmentioning
confidence: 99%
“…Images are centralised in three interpretation centres where teams of radiologists use the same tools to interpret images and report findings to emergency physicians. Moreover, resource organisation and structured processes, particularly chest CT, provide high diagnostic accuracy with strong inter-observer agreement between on-call teleradiologists with varying degrees of experience and senior radiologists [4]. Indeed, thanks to our structured organisation, we already showed that teleradiology enabled us to monitor the impact of the COVID-19 pandemic management on emergency activities, showing a global decrease in the population's use of care during the first lockdown in France [5].…”
Section: Introductionmentioning
confidence: 76%
“…We would have had to exclude all the observations from the first wave. However, we believe that using the French Society of Radiology scoring system could provide more powerful predictors in future radiological forecasting models-although strongly suggestive/compatible conclusions with COVID-19 diagnosis do not systematically mean positive RT-PCR despite the excellent accuracy of the French Society of Radiology scoring system [4]. Finally, it is important to consider that existing indicators based on hospitalisations should become less accurate with vaccination, necessitating original indicators.…”
Section: Table 4 Final Predictive Modelsmentioning
confidence: 91%
“…have demonstrated that IMADIS structuration enables to organize systematic second readings of whole body CT scanners in multiple traumas patients, with good diagnostic performances of OCTRs whatever the amount of activity and the hours of the day 32 . Regarding the OCTRs’ accuracy for diagnosing COVID-19, Nivet et al have also shown that implementing the semi-quantitative assessment as proposed by SFR was feasible and provided high sensitivity (0.92), specificity (0.75–0.84), PPV (0.77–0.84) and NPV (0.91–0.92) depending on the reading and when considering the indeterminate/compatible group as positive 12 .…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, our population represents a real-life emergency cohort and some patients could have had non-infectious diseases (: conclusion (2)), or non-pulmonary infections for instance (: conclusion (1)), in addition to non-COVID-19 lung infectious diseases (: conclusion (3)). Finally, although widely used and significantly reproducible over multiple raters, the radiological features were qualitatively or semi-quantitatively assessed, which introduces a risk of subjectivity and could bias the performances of the model in other validation cohorts 12 .…”
Section: Discussionmentioning
confidence: 99%